Primary Pneumatosis Intestinalis of Small Bowel: A Case of a Rare Disease. (17th November 2014) - Berritto, Daniela; Crincoli, Raffaello; Iacobellis, Francesca; Iasiello, Francesca; Pizza, Nunzia Luisa; Lassandro, Francesco; Musto, Lanfranco; Grassi, Roberto
Abstract : Pneumatosis intestinalis (PI) is a condition in which multiple gas-filled cysts are located in the bowel wall; it can represent a wide spectrum of diseases and a variety of underlying diagnoses. The present report describes the case of an 86-year-old man with symptomatic primary PI of small bowel treated with surgical approach after periodic episodes of cysts rupture and superimposed inflammation revealed on the basis of a clinical suspicion thanks to abdominal computed tomography. Moreover, after one year of followup, there has been no recurrence of digestive symptoms.